2011
DOI: 10.1080/02687038.2011.570933
|View full text |Cite
|
Sign up to set email alerts
|

Coping resources in individuals with aphasia

Abstract: Communication difficulties and other stroke sequalae may cause individuals with aphasia (IWA) greater psychological and physiological stress than the general population. Indeed, Laures-Gore, Hamilton, and Matheny (2007) found that IWA have greater perceived stress when compared to healthy controls. Increased levels of psychological stress are associated with negative health outcomes, including poor immune system function and increased risk for disease (Selye,1955;McEwen, 1998). Individuals can reduce the damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…Because the perception of stress partially depends on an individual’s coping resources (e.g., acceptance, confidence, financial freedom, social support, tension control, stress monitoring), mental health and health professionals could focus on the coping resources available to patients with higher perceived stress scores. This suggestion has been addressed previously by Dubay, Laures-Gore, Matheny, & Romski (2011); in left hemisphere stroke patients with aphasia and right hemisphere stroke patients, perceived coping resources were fewer than neurologically intact individuals. Acceptance [the understanding that weaknesses, flaws, and frustrations are normal and should not be a subject of focus (Curlette, Aycock, Matheny, Pugh, & Taylor, 1992)] was especially diminished in both stroke groups.…”
Section: Discussionmentioning
confidence: 67%
“…Because the perception of stress partially depends on an individual’s coping resources (e.g., acceptance, confidence, financial freedom, social support, tension control, stress monitoring), mental health and health professionals could focus on the coping resources available to patients with higher perceived stress scores. This suggestion has been addressed previously by Dubay, Laures-Gore, Matheny, & Romski (2011); in left hemisphere stroke patients with aphasia and right hemisphere stroke patients, perceived coping resources were fewer than neurologically intact individuals. Acceptance [the understanding that weaknesses, flaws, and frustrations are normal and should not be a subject of focus (Curlette, Aycock, Matheny, Pugh, & Taylor, 1992)] was especially diminished in both stroke groups.…”
Section: Discussionmentioning
confidence: 67%
“…Hilari and colleagues (2010) reported that a higher proportion of stroke survivors with aphasia (93%) experienced psychological distress than non-aphasic stroke survivors (50%) 3 months after the stroke [ 10 ]. Compared with people with no neurological damage or with right brain damage, PWA perceived themselves as less able to reduce tension built up due to stress by relaxing or managing their thoughts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve articles included attitude and outlook as key components of resilience or like terms. First, acknowledgement and acceptance of the change experienced by the individual (Brown et al, 2011b; DuBay et al, 2011; Moss et al, 2021; Panda et al, 2021), including grieving-related losses (Mumby & Roddam, 2021), were highlighted in several articles. Other articles featured a mindset of growth and learning, described as accommodating and managing changes and limitations (Grohn et al, 2012; Moss et al, 2021; Panda et al, 2021), and/or a willingness to adapt and learn new things and a positive way of life (Brown et al, 2011a; Grohn et al, 2014; Hinckley, 2015; Moss et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Five articles mentioned the association between resilience and/or similar terms and access to treatment (Bronken et al, 2012;Brown et al, 2011a;Wray et al, 2019Wray et al, , 2020 and/or education and information (Bronken et al, 2012;Grohn et al, 2014). Finally, three articles noted that other resources or factors, such as assistive technology, financial security, and communicative participation in non-distracting environments, may also associate with resilience (Brown et al, 2010;DuBay et al, 2011;Harmon, 2020).…”
Section: External/behavioral Responsesmentioning
confidence: 99%